2009
DOI: 10.1242/jeb.025882
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional characterization of four aquaporin water channels from the European eel (Anguilla anguilla)

Abstract: SUMMARYThe European eel is a euryhaline teleost which has been shown to differentially up-and downregulate aquaporin (AQP) water channels in response to changes in environmental salinity. We have characterized the transport properties of four aquaporins localized to osmoregulatory organs -gill, esophagus, intestine and kidney. By sequence comparison these four AQP orthologs resemble human AQP1 (eel AQP1), AQP3 (eel AQP3) and AQP10 (AQPe). The fourth member is a duplicate form of AQP1 (AQP1dup) thought to arise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…The AQP10 protein was reported in the brush-border membrane of absorptive enterocytes of the upper villus Laforenza et al, 2010), whereas other authors have demonstrated the presence of two AQP10 isoforms, one located in gastroentero-pancreatic endocrine cells and another truncated form (named AQP10v), in capillary endothelial cells of villi (Li et al, 2005). In humans, zebrafish and eel the ortholog is permeable to water, glycerol and urea (Ishibashi et al, 2002;MacIver et al, 2009;Tingaud-Sequeira et al, 2010). Recently, it was also found in human adipocytes, where it is co-expressed with two other glyceropores, AQP3 and AQP7 (Rodríguez et al, 2011;Laforenza et al, 2013), and may play a major role in glycerol metabolism.…”
Section: Research Articlementioning
confidence: 99%
“…The AQP10 protein was reported in the brush-border membrane of absorptive enterocytes of the upper villus Laforenza et al, 2010), whereas other authors have demonstrated the presence of two AQP10 isoforms, one located in gastroentero-pancreatic endocrine cells and another truncated form (named AQP10v), in capillary endothelial cells of villi (Li et al, 2005). In humans, zebrafish and eel the ortholog is permeable to water, glycerol and urea (Ishibashi et al, 2002;MacIver et al, 2009;Tingaud-Sequeira et al, 2010). Recently, it was also found in human adipocytes, where it is co-expressed with two other glyceropores, AQP3 and AQP7 (Rodríguez et al, 2011;Laforenza et al, 2013), and may play a major role in glycerol metabolism.…”
Section: Research Articlementioning
confidence: 99%
“…To test the effect of HgCl 2 on swelling rate, vesicles were exposed to artificial seawater (ASW; 545 mmol l −1 NaCl), SSW and distilled water buffered with 5.0 mmol l −1 Tris under control conditions and after treatment with 1 mmol l −1 HgCl 2 (MacIver et al, 2009).…”
Section: Triton X-100 and Hgcl 2 Exposurementioning
confidence: 99%
“…Observations of elevated mRNA expression following seawater transfer, elevated AQP1 protein abundance in intestinal tissue following seawater acclimation and, finally, apical as well as basolateral localization of the protein suggest a role in transepithelial water movement (Aoki et al, 2003;Martinez et al, 2005a;Martinez et al, 2005b;Raldua et al, 2008). It has been demonstrated that AQP1 genes from fish confer water permeability in expression systems (MacIver et al, 2009), including AQP1a from F. heteroclitus (Tingaud-Sequeira et al, 2009), but despite the above observations, direct evidence for a role for AQP1 in intestinal water absorption has been lacking. Consistent with this view, Cerda and Finn caution that the relative contribution of aquaporin-mediated transcellular flux versus paracellular flux is largely unknown (Cerda and Finn, 2010).…”
Section: A Role For Aquaporins In Intestinal Water Absorption In Fishmentioning
confidence: 99%
“…, the same as that required to inhibit fish aquaporins in an oocyte expression system (MacIver et al, 2009). However, 10…”
Section: A Role For Aquaporins In Intestinal Water Absorption In Fishmentioning
confidence: 99%